In-Vitro Comparative Study to Evaluate The Marginal Fit of Two Types of Provisional Crowns Cemented with Different Luting Cements. (Journal of Hama University, 2021)
When we prepare the teeth, we remove some of tooth tissues or restorations form the abutment. and after we finish the preparation, the tooth will be uncover and we can't make a proper final restoration immediately because of the time that we need to manufacture the restoration in the laboratory so the practices should give their patient a provisional restoration covers the space of the final one .so that the provisional restoration in consider ed a main part in treatment of plan for fixed prosthodontics patient and this restoration must have a good marginal fit ,and after the adhesive it reduce the marginal leakage to protect the abutment and periodontal tissue. The aim of the study is to compare and evaluate marginal adaptation for provisional restoration manufactured by CAD-CAM technology and manufactured by the direct method and adhesive with cements with eugenol or free of it. The research sample consisted of / 40 / newly extracted premolars that were divided randomly into four equal groups according to the method used in the manufacture of temporary restoration and the substance of its adhesive as follows: (The first group: restoration by the direct method and cement containing eugenol /Trantemp and temp bond/) (The second group: restoration by the direct method and cement that does not contain eugenol /Trantemp and temp bond NE/) (Group III: restoration by the indirect method and cement containing eugenol /PMMA and temp bond/) (Group IV: restoration by the indirect method and cement that does not contain eugenol and /PMMA temp bond NE/).The marginal applicability was evaluated before and after cementation :The results showed that the indirect temporary restoration has achieved better marginal fit, where the marginal gap was less before and after cementation, when compared with direct temporary restoration,In addition, it was found that there was a direct effect of adhesive cement on increasing the marginal gap after cementation and when we study the marginal leakage, the indirect restoration cemented with free Eugenol cement has less marginal leakage than the other group